2017
DOI: 10.1063/1.4978032
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary tunability of high-frequency devices using Hf0.3Zr0.7O2 ferroelectric at very low applied voltages

Abstract: This paper presents the applications of the Hf 0.3 Zr 0.7 O 2 ferroelectric with a thickness of 10 nm for tuning high-frequency devices such as filters, phase shifters, and phased antenna arrays in the X band when the low bias voltages in the range À3 V-þ3 V are applied. In this respect, we show that a bandpass filter shifts its central frequency located at 10 GHz with 3 GHz, a phase shifter produces a phase difference of about 60 degrees in the X band, while the antenna array formed by two patched antennas is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…Thus, amplifiers, filters, and antenna arrays can be tuned by ferroelectrics, but this approach is almost abandoned today due to the fact that the applied DC voltages attain tens of volts. However, we have demonstrated that extraordinary tunability of microwave devices can be obtained at very low DC voltages, not exceeding ± 3 V . In this respect, we have demonstrated that the phase shift of an interdigitated phase shifter in coplanar technology, fabricated at the wafer scale on HfZrO/high resistivity Si, is 60 0 at 1 GHz and 13 0 at 10 GHz, if the applied DC voltage is within the range ± 3 V. The DC voltage is so low that it can be provided by a battery .…”
Section: D Ferroelectrics and Their Applicationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, amplifiers, filters, and antenna arrays can be tuned by ferroelectrics, but this approach is almost abandoned today due to the fact that the applied DC voltages attain tens of volts. However, we have demonstrated that extraordinary tunability of microwave devices can be obtained at very low DC voltages, not exceeding ± 3 V . In this respect, we have demonstrated that the phase shift of an interdigitated phase shifter in coplanar technology, fabricated at the wafer scale on HfZrO/high resistivity Si, is 60 0 at 1 GHz and 13 0 at 10 GHz, if the applied DC voltage is within the range ± 3 V. The DC voltage is so low that it can be provided by a battery .…”
Section: D Ferroelectrics and Their Applicationsmentioning
confidence: 91%
“…The NDR of the ballistic graphene FET with inclined gate at V TG = 0 V (red dashed line), 0.5 V (blue dotted line) and 1 V (solid red line). Reproduced with permission . Copyright 2017, Institute of Physics, UK.…”
Section: Graphene Devices and Circuits At The Waferscalementioning
confidence: 99%
“…HfO 2 doped with Zr) and some applications are already based on their properties, such as intense piezoelectric properties [4] and pyroelectric response [5]. We have recently shown theoretically that an extraordinary tunability can be obtained based on Hf x Zr 1 − x O 2 ferroelectrics [6] and we have demonstrated experimentally that phase shifters with phase shifts larger than 60° at 1 GHz and 13° at 10 GHz, at maximum applied DC voltages of ±3 V, are working with moderate losses [7]. We are continuing this research demonstrating that the phased array in Fig.…”
Section: Electromagnetic Design and Fabrication Of The Ferroelectric‐mentioning
confidence: 99%
“…Today there is a stable interest in ferroelectric (FE) materials for tunable microwave (MW) applications caused by the dependence of dielectric permittivity of ferroelectrics on the strength of applied electric field [1][2][3][4]. The perspective properties of ferroelectrics at microwaves are high dielectric nonlinearity, low losses, fast switching time, low power consumption, and possibility to work under the high level of operating power [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%